2014
DOI: 10.1111/joim.12328
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota‐dependent metabolite trimethylamine‐N‐oxide is associated with disease severity and survival of patients with chronic heart failure

Abstract: Objectives. Recent metabolomic, experimental and clinical studies have demonstrated that trimethylamine-N-oxide (TMAO), a microbiotadependent metabolite from dietary phosphatidylcholine and carnitine, is a strong predictor of coronary artery disease (CAD). This finding suggests a link between the gut microbiota and atherosclerosis. The potential impact of TMAO in chronic heart failure (HF) is unknown. We hypothesized that TMAO levels would provide prognostic information about adverse outcomes in chronic HF.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
318
7
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(354 citation statements)
references
References 25 publications
23
318
7
6
Order By: Relevance
“…The association of the microbiota with diseases such as cancer (31), diabetes (32), and cardiovascular diseases (33) has been demonstrated. TMAO is a metabolite created in the host liver from microbiota-produced TMA, and it has been associated with several diseases (3)(4)(5)(6)(7)(8)(9)(10). TMA production in the intestine can be suppressed by antibiotics (34,35), but this effect is not complete, and long-term antibiotic treatment may lead to an imbalance in the microbiota (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of the microbiota with diseases such as cancer (31), diabetes (32), and cardiovascular diseases (33) has been demonstrated. TMAO is a metabolite created in the host liver from microbiota-produced TMA, and it has been associated with several diseases (3)(4)(5)(6)(7)(8)(9)(10). TMA production in the intestine can be suppressed by antibiotics (34,35), but this effect is not complete, and long-term antibiotic treatment may lead to an imbalance in the microbiota (36).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of TMAO, which are produced from choline (6) and carnitine (3) with the assistance of the intestinal microflora, have been shown to be a cause of atherosclerosis in mice. Studies with human volunteers (3,7) have confirmed TMA production from carnitine and choline by the intestinal microflora, and clinical data cross-examinations have associated high levels of TMAO with an elevated risk of atherosclerosis (7), severe heart failure (8), and renal failure (9). Lowering TMA and TMAO levels in humans could therefore have potentially preventive and therapeutic effects on trimethylaminuria and cardiovascular diseases.…”
Section: Trimethylamine (Tma)mentioning
confidence: 98%
“…18 Two other observational studies linked plasma TMAO levels to severity of heart failure. Both a Norwegian study of 155 heart failure patients 25 and a North American study of 112 patients 26 reported associations between higher plasma TMAO, symptom severity and risk of all-cause mortality or heart transplantation over a 5-year follow-up period. 25,26 Importantly, increased age, previous myocardial infarction 25 and reduced kidney function assessed by estimated glomerular filtration rate (eGFR) strongly predicted blood TMAO levels.…”
Section: Tmao As a Mediator Of CV Disease: Clinical Datamentioning
confidence: 99%
“…L -carnitine plays an important role in energy production from FA. It also acts in the removal of mitochondrial metabolism products and participates in cellular defense against apoptosis and ROS [13]. Its homeostasis is maintained through dietary ingestion, endogenous synthesis, transport to tissues and renal excretion [14,15].…”
Section: Introductionmentioning
confidence: 99%